Reconciling the differences between top‐down and bottom‐up estimates of nitrous oxide emissions for the U.S. Corn Belt. Issue 3 (18th August 2013) - Griffis, T. J.; Lee, X.; Baker, J. M.; Russelle, M. P.; Zhang, X.; Venterea, R.; Millet, D. B.
<x xml:space="preserve">Abstract</x> [1] Nitrous oxide (N2O) is a greenhouse gas with a large global warming potential and is a major cause of stratospheric ozone depletion. Croplands are the dominant source of N2O, but mitigation strategies have been limited by the large uncertainties in both direct and indirect emission factors (EFs) implemented in "bottom‐up" emission inventories. The Intergovernmental Panel on Climate Change (IPCC) recommends EFs ranging from 0.75% to 2% of the anthropogenic nitrogen (N) input for the various N2O pathways in croplands. Consideration of the global N budget yields a much higher EF ranging between 3.8% and 5.1% of the anthropogenic N input. Here we use 2 years of hourly high‐precision N2O concentration measurements on a very tall tower to evaluate the IPCC bottom‐up and global "top‐down" EFs for a large representative subsection of the United States Corn Belt, a vast region spanning the U.S. Midwest that is dominated by intensive N inputs to support corn cultivation. Scaling up these results indicates that agricultural sources in the Corn Belt released 420±50 Gg N (mean ±1 standard deviation; 1 Gg =109 g) in 2010, in close agreement with the top‐down estimate of 350±50 Gg N and 80% larger than the bottom‐up estimate based on the IPCC EFs (230 ± 180 Gg N). The large difference between the tall tower measurement and the bottom‐up estimate implies the existence of N2O emission hot spots or missing sources within the landscape that are not fully accounted for in the IPCC and other bottom‐up emission inventories. Reconciling these differences is an important step toward developing a practical mitigation strategy for N2O.